Long-Term Effects of Haematopoietic Stem Cell Transplantation after Pediatric Cancer: A Qualitative Analysis of Life Experiences and Adaptation Strategies - Lahaye, Magali; Aujoulat, Isabelle; Vermylen, Christiane; Brichard, Bénédicte (Frontiers in Psychology, 2017)
Haematopoietic stem cell transplantation improves the survival rate of children and adolescents with malignant and non-malignant conditions; however the physical, psychological and social burden of such a procedure is considerable both during and after treatment. The present qualitative study investigated the long-term effects of haematopoietic stem cell transplantation after pediatric cancer. Thirty adolescent and young adult survivors (Mage = 23.61 years, SD = 5.21) participated in individual interviews and speak about their life experiences following their treatment and strategies they use to deal with their past medical experiences and the long-term sequelae. Our results showed the presence of ongoing physical and psychosocial consequences of their past illness and its treatments with wide ranging psychosocial impacts, such as affected self-image, social withdrawal, sense of lack of choice, and need for specific attention. Different strategies were reported to overcome these consequences, such as talking about illness, giving a sense to their past medical experiences, and developing meaningful social relationships. Clinical and research implications are also discussed.